Dialog dan Kerjasama Antariman sebagai Upaya Pemaknaan Nilai Agama dalam Menangkal Radikalisme - Mochamad Ziaul Haq; Yunika Sari (Journal of Religion and Social Transformation, 2023)
This study aims to discuss the study of religion and radicalism in the realm that focuses on religion as conflict resolution and peacebuilding in an effort to ward off radicalism. This research method is qualitative in nature to describe and systematically interpret the facts of radicalism, using relevant literature study methods, which examine library sources such as research reports (thesis, journals), books and other supporting data related to the topic of religious radicalism, in addition to a descriptive analysis approach that places more emphasis on reviews related to the theme that has been determined and then described according to the formulation, and the results are summarized briefly and clearly. The discussion of this research includes the understanding of religious radicalism, indications and implications of radicalism, and religion as conflict resolution and peace. This study concludes that radicalism is an understanding that requires major changes and reforms by using violence. So there is a ned for conflict resolution to overcome or prevent the occurrence of radicalism, namely the concept of a religion of peace that presents the concept of inter-faith dialogue.